Analysis of the Dynamic Balance Condition of Crank-group Mechanism - Cao Jujiang; Wu Yao; Yan Weiliang (Jixie chuandong)
Aiming at overcoming the deficiency of dynamic balance of crank- group mechanism,combining the mass moment substitution method and the momentum moment substitution method,the complete balance conditions of swing force and swing torque of crank- group driving mechanism are derived. The expressions of the additional mass moment and additional momentum moment of connecting rod truss that is equivalent in adjacent cranks and the dynamic balance conditions of two pair rod tree system can be obtained by solving a linear equation set. It is also proved that such institutions can achieve the balance of force and moment by adding the counterweight without inertia weight mechanism,the application of this dynamic balance method of crank- group mechanism has a theoretical significance for designing the physical prototype experiment and choosing the parameters of counterweight.